Remote triggering of TGF-β/Smad2/3 signaling in human adipose stem cells laden on magnetic scaffolds synergistically promotes tenogenic commitment. (1st September 2020) - Matos, Ana M.; Gonçalves, Ana I.; Rodrigues, Márcia T.; Miranda, Margarida S.; Haj, Alicia J. El; Reis, Rui L.; Gomes, Manuela E.
Abstract: Injuries affecting load bearing tendon tissues are a significant clinical burden and efficient treatments are still unmet. Tackling tendon regeneration, tissue engineering strategies aim to develop functional substitutes that recreate native tendon milieu. Tendon mimetic scaffolds capable of remote magnetic responsiveness and functionalized magnetic nanoparticles (MNPs) targeting cellular mechanosensitive receptors are potential instructive tools to mediate mechanotransduction in guiding tenogenic responses. In this work, we combine magnetically responsive scaffolds and targeted Activin A type II receptor in human adipose stem cells (hASCs), under alternating magnetic field (AMF), to synergistically facilitate external control over signal transduction. The combination of remote triggering TGF-β/Smad2/3 using MNPs tagged hASCs, through magnetically actuated scaffolds, stimulates overall expression of tendon related genes and the deposition of tendon related proteins, in comparison to non-stimulated conditions. Moreover, the phosphorylation of Smad2/3 proteins and their nuclear co-localization was also more evident. Overall, biophysical stimuli resulting from magnetic scaffolds and magnetically triggered cells under AMF stimulation modulate the mechanosensing response of hASCs towards tenogenesis, holding therapeutic promise. Statement of Significance: The concept of magnetically-assisted tissue engineering may assist the development of innovative solutions to treat tendon disorders upon remote control of biological processes as cell migration or differentiation. Herein, we originally combine a fibrous aligned superparamagnetic scaffold, based on a biodegradable polymeric blend of starch and poly-ɛ-caprolactone incorporating magnetic nanoparticles (MNPs), and human adipose stem cells (hASCs) labelled with MNPs functionalized with anti-activin receptor type IIA (ActRIIA). Constructs were stimulated using alternating magnetic field (AMF), to activate the ActRIIA and subsequent induction of TGF-β signaling, through Smad2/3 phosphorylation cascade, enhancing the expression of tendon-related markers. Altogether, these findings contribute with powerful bio-magnetic approaches to activate key tenogenic pathways, envisioning future translation of magnetic biomaterials into regenerative platforms for tendon repair. Graphical abstract: Image, graphical abstract